EPV 5. Tractography of hippocampal association fibers in patients with hippocampal sclerosis and temporal lobe epilepsy. Issue 9 (September 2016) - Hammen, E.-T.; Nakagawa, J.; Reisert, M.; Urbach, H.; Schulze-Bonhage, A.; Egger, K.
Abstract : Introduction: Temporal lobe epilepsy (TLE) is the most common focal epilepsy and is often caused by hippocampal sclerosis (HS) (Babb and Brown, 1987 ). As the hippocampal formation is an essential part of the Papez circuit, we investigated whether HS is associated with alterations of the Papez circuit network. The aim of our study was to analyse alterations of fibers connecting the affected hippocampus by applying a new Diffusion-weighted MRI (DTI) method called "Global Tracking". Methods: Whole brain "Global Tracking" based on high-angular diffusion weighted imaging in 61 directions was performed on a 3 Tesla MRI scanner in 20 TLE-patients with unilateral ( n = 17) and bilateral ( n = 3) hippocampal sclerosis as well as in 20 healthy controls individually matched for age, gender and handedness as reference group. The fiber tracts of interest, i.e. whole cingulum and the hippocampus-associated part of the cingulum, respectively, were selected on color coded DTI images superimposed on a T1w 3D sequence. The fiber tracts were selected on color coded Fractional Anisotropy (FA) maps using a MATLAB-based software package FiberViewerTool (Reisert et al., 2011 ) (Fig. 1 ). From these individually derived tracts the numbers of streamlines were extracted and statistically evaluated using paired Wilcoxon signed rank tests. Results: Streamline counts of fibers between pathologically altered hippocampal structures and the whole cingulate gyrus (cgc; p = 0.000021) and the hippocampus-associated tract of the cingulate gyrus (chc; p = 0.00054), respectively, were significantly lower in patients than in the corresponding hemisphere of individually matched healthy controls (Figs. 3 and 4). The same was true when comparing the corresponding fibers (cgc: p = 0.0021/chc: p = 0.00098) in the hemisphere contralateral to the hippocampal pathology in patients and controls (Figs. 5 and 6) Conclusion: The ability to delineate the substructures of the Papez circuit offers the basis for monitoring structural white matter changes in patients with HS. Our results support the notion that we have to consider focal lesions like HS in the CNS in the context of larger alterations in the whole intracerebral network.